Coronavirus virus disease (COVID-19) outbreak Africa [electronic resource] - World Health Organization. Regional Office for Africa (Brazzaville, Congo World Health Organization, Regional Office for Africa, 2020)
COVID-19 is an emerging, rapidly evolving situation. Get the latest public health information from this site.
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Open education; Open access publishing; Education, Higher; COVID-19 (Disease) -- Research -- Electronic information resources; COVID-19 (Disease) -- Africa -- Electronic information resources; Open access publishing; Algeria -- COVID-19 (Disease) -- Electronic information resources; Angola -- COVID-19 (Disease) -- Electronic information resources; Benin -- COVID-19 (Disease) -- Electronic information resources; Botswana -- COVID-19 (Disease) -- Electronic information resources; Burkina Faso -- COVID-19 (Disease) -- Electronic information resources; Burundi -- COVID-19 (Disease) -- Electronic information resources; Cabo Verde -- COVID-19 (Disease) -- Electronic information resources; Cameroonl -- COVID-19 (Disease) -- Electronic information resources; Central African Republic -- COVID-19 (Disease) -- Electronic information resources; Chad -- COVID-19 (Disease) -- Electronic information resources; Comoros -- COVID-19 (Disease) -- Electronic information resources; Congo -- COVID-19 (Disease) -- Electronic information resources; Cote d?Ivoire -- COVID-19 (Disease) -- Electronic information resources; Democratic Republic of Congo -- COVID-19 (Disease) -- Electronic information resources; Equatorial Guinea -- COVID-19 (Disease) -- Electronic information resources; Eritrea -- COVID-19 (Disease) -- Electronic information resources; Eswatini -- COVID-19 (Disease) -- Electronic information resources; Ethiopia -- COVID-19 (Disease) -- Electronic information resources; Gabon -- COVID-19 (Disease) -- Electronic information resources; Gambia -- COVID-19 (Disease) -- Electronic information resources; Ghana -- COVID-19 (Disease) -- Electronic information resources; Guinea -- COVID-19 (Disease) -- Electronic information resources; Guinea-Bissau -- COVID-19 (Disease) -- Electronic information resources; Kenya -- COVID-19 (Disease) -- Electronic information resources; Lesotho -- COVID-19 (Disease) -- Electronic information resources; Liberia -- COVID-19 (Disease) -- Electronic information resources; Madagascar -- COVID-19 (Disease) -- Electronic information resources; Malawi -- COVID-19 (Disease) -- Electronic information resources; Mali -- COVID-19 (Disease) -- Electronic information resources; Mauritania -- COVID-19 (Disease) -- Electronic information resources; Mauritius -- COVID-19 (Disease) -- Electronic information resources; Mozambique -- COVID-19 (Disease) -- Electronic information resources; Namibia -- COVID-19 (Disease) -- Electronic information resources; Niger -- COVID-19 (Disease) -- Electronic information resources; Nigeria -- COVID-19 (Disease) -- Electronic information resources; Rwanda -- COVID-19 (Disease) -- Electronic information resources; Sao Tome and Principe -- COVID-19 (Disease) -- Electronic information resources; Senegal -- COVID-19 (Disease) -- Electronic information resources; Seychelles -- COVID-19 (Disease) -- Electronic information resources; Sierra Leone -- COVID-19 (Disease) -- Electronic information resources; South Africa -- COVID-19 (Disease) -- Electronic information resources; South Sudan -- COVID-19 (Disease) -- Electronic information resources; Togo -- COVID-19 (Disease) -- Electronic information resources; Uganda -- COVID-19 (Disease) -- Electronic information resources; United Republic of Tanzania -- COVID-19 (Disease) -- Electronic information resources; Zambia -- COVID-19 (Disease) -- Electronic information resources; Zimbabwe -- COVID-19 (Disease) -- Electronic information resources